ANALISIS POTENSI MAKANAN TRADISIONAL SOP LOMPONG DI RUMAH MAKAN SAUNG ELING SEBAGAI DAYA TARIK WISATA KULINER DI BOGOR, JAWA BARAT - Angel; Prayogo Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze to the appeal of traditional culinary tourism at Saung Eling and to identify the internal and external factors influencing it’s development as a traditional culinary tourism destination in Bogor. Culinary tourism is currently a growing tourism sector, offering not only food but also cultural experiences and a unique atmosphere for tourists. This study used a descriptive qualitative approach to understand the appeal of traditional culinary tourism at Saung Eling in depth. Data collection techniques included observation, interviews, documentation, and literature review. Informants for this study included the management, visitor, and the local community around Saung Eling Restaurant. The data obtained were than analyed descriptively through the process of data reduction, data presentation, and drawing conclusions to describe the conditions and potential of traditional culinary tourism in Saung Eling. The resluts ofthe study indicate that the appeal ofSaung Eling lies in it’s traditional concept, comfortable natural setting, Sundanese cuisine, and the culinary tourism experience experienced by visitors. The traditional food at Saung Eling Restaurant has the potential to become a major culinary tourism attraction through it’s unique flavors, connection to local culture, authentic menu items, dining experiences, and memorable experiences for visitors. There are several weakneeses such as limited digital promotion and certain facilities that still need to be developed. On the other hand, the growing public interest in traditional culinary tourism and the development of social media present opportunities for Saung Eling to expand it’s tourism appeal. Based on research, Saung Eling has significant potential to develop as a traditional culinary tourism destination in Bogor while maintaining it’s local cultural identity and traditional concepts.